Cantharidin: a double-edged sword in medicine and toxicology - Zhang, Jie; Tian, Tongtong; Li, Canyu; Liu, Yong; Wang, Yunyun; Liu, Ling; Liu, Liang; Yao, Yufeng (Frontiers in Pharmacology, 2025)
Cantharidin (CTD), a natural terpenoid toxin secreted by blister beetles, acts as a potent inhibitor of protein phosphatase. As the principal active component of Mylabris, a traditional Chinese medicine, CTD has attracted considerable interest due to its dual properties, combining potent anti-tumor activity with significant toxicity. Contemporary pharmacological research demonstrates that CTD inhibits the growth and proliferation of diverse cancer cells lines. It exhibits antibacterial and antiparasitic properties, and demonstrates pesticidal activity in agricultural applications. Despite these benefits, CTD exhibits a prominent double-edged profile, marked by severe toxic effects, including cardiotoxicity, nephrotoxicity, gastrointestinal toxicity, and reproductive toxicity. Our prior research has identified the heart and liver as primary targets of CTD’s acute toxicity, where it induces apoptosis and necrosis of cardiomyocytes and hepatocytes. Recent efforts to mitigate its toxicity while preserving efficacy have focused on the structural modifications of CTD and the development of its derivatives. Additionally, CTD has been demonstrated to enhance anti-tumor efficacy when combined with other drugs, particularly against certain drug-resistant tumors. This review comprehensively evaluates CTD’s pharmacology and toxicology, synthesizes pertinent toxicological data, and explores strategies for toxicity reduction to guide future research.